Immunolocalization of Ferroportin in Healthy and Anemic Mice - D'anna, Maria Cecilia (2009)
Ferroportin (FPN), the only iron exporter identified to date, participates in iron release from enterocytes and macrophages, regulating its absorption and recycling. We used a murine model of experimental hemolytic anemia to study adaptive changes in the localization of FPN in duodenum, liver, and spleen. FPN was assessed by IHC in healthy and anemic mice using rabbit anti-mouse FPN polyclonal antibodies. Goat-labeled polymer-horseradish peroxidase anti-rabbit Envision+System (DAB) was used as secondary antibody. Tissue iron was studied by Prussian blue iron staining. Anemia evolution and erythropoietic recovery was assessed using conventional hematological tests. Healthy mice showed mainly supranuclear expression of FPN in enterocytes and a weak basolateral expression, whereas in anemic mice, the expression was detected mainly at the basolateral membrane (days 4 and 5). Red pulp macrophages of healthy mice showed FPN-hemosiderin colocalization. In the liver of healthy mice, FPN was mainly cytoplasmic, whereas in anemic mice, it was redistributed to the cell membrane. Our findings clearly show that anemia induces adaptive changes in FPN expression, contributing to anemia restoration by increasing available iron. FPN expression in the membrane is the main pathway of iron release. Our data indicate that iron homeostasis in vivo is maintained through the coordinated expression of this iron exporter in both intestinal and phagocytic cells.